HVPE of Scandium Nitride on 6H-SiC(0001) - Edgar, James H.; Bohnen, T.; Hageman, P. R. (My University, 2008)
The epitaxy of scandium nitride deposited by hydride vapor phase epitaxy on 6HSiC( 0001) substrates is reported. The structure and composition of the deposited films were dependent on both the scandium metal source and substrate temperatures. At substrate temperatures between 800 to 900 °C, the ScN exhibited a single (111) orientation. At substrate temperatures of 1000 °C and above, the films were mixtures of (100) and (111) orientations. Aluminum was detected by EDAX in the ScN films when the scandium source temperature was greater than 900 °C, presumably due to the reaction between scandium and the alumina reactor tube. Chlorine was detected in the films, and its concentration increased as the scandium source temperature was decreased from 1000 °C to 800 °C.
Keywords: Impurities; X-ray diffraction; Hydride vapor phase epitaxy; Nitrides; Semiconducting III-V materials